Retinoic acid signaling regulates spatiotemporal specification of human green and red cones. - Sarah E Hadyniak; Joanna F D Hagen; Kiara C Eldred; Boris Brenerman; Katarzyna A Hussey; Rajiv C McCoy; Michael E G Sauria; James A Kuchenbecker; Thomas Reh; Ian Glass; Maureen Neitz; Jay Neitz; et al. (PLoS Biology, 2024)
Trichromacy is unique to primates among placental mammals, enabled by blue (short/S), green (medium/M), and red (long/L) cones. In humans, great apes, and Old World monkeys, cones make a poorly understood choice between M and L cone subtype fates. To determine mechanisms specifying M and L cones, we developed an approach to visualize expression of the highly similar M- and L-opsin mRNAs. M-opsin was observed before L-opsin expression during early human eye development, suggesting that M cones are generated before L cones. In adult human tissue, the early-developing central retina contained a mix of M and L cones compared to the late-developing peripheral region, which contained a high proportion of L cones. Retinoic acid (RA)-synthesizing enzymes are highly expressed early in retinal development. High RA signaling early was sufficient to promote M cone fate and suppress L cone fate in retinal organoids. Across a human population sample, natural variation in the ratios of M and L cone subtypes was associated with a noncoding polymorphism in the NR2F2 gene, a mediator of RA signaling. Our data suggest that RA promotes M cone fate early in development to generate the pattern of M and L cones across the human retina.